Earning the Rockies [compact disc, unabridged] : how geography shapes America's role in the world - Kaplan, Robert D., 1952- (HighBridge Audio, 2017)
As a boy, Robert D. Kaplan listened to his truck-driver father's evocative stories about traveling across America as a young man, travels in which he learned to understand the country from a ground-level perspective. Now, Kaplan undertakes his own cross-country journey to recapture an appreciation and understanding of American geography that is often lost in the jet age. The history of westward expansion is examined here in a new light, not just a story of genocide and individualism, but also of communalism and a respect for the limits of a water-starved terrain, to understand how settling the West shaped national character, and how it should shape foreign policy.